APAKAH FINANCIAL DAN OPERATIONAL HEDGING EFEKTIF MENGURANGI EKSPOSUR NILAI TUKAR? - Sasmitapura, Angga; Djajadikerta, Hamfri (Jurnal Akuntansi Kontemporer, 2021)
In the midst of regulators' efforts to deepen the market by encouraging foreign exchange derivative transactions, this study aims to observe the effect of these derivative instruments from company perspective in reducing exchange rate exposures. In addition to hedge using derivative instruments (financial hedging), this study also observed hedging performed through firm’s operational activity (operational hedging) with control variables of export sales and foreign debt. The research object is manufacturing companies listed in IDX (Indonesia Stock Exchange) during 2010-2018 using panel data regression as data analysis method. Empirical results show that financial hedging reduce exchange rate exposures faced by companies while operational hedging has no effect. Export sales provide positive exchange rate exposures and foreign debt provide negative exchange rate exposures.